The role of ALOX5AP, LTA4H and LTB4R polymorphisms in determining baseline lung function and COPD susceptibility in UK smokers - Tulah Asif S; Parker Stuart G; Moffatt Miriam F; Wardlaw Andrew J; Connolly Martin J; Sayers Ian (BMC, 2011)
Abstract Background We have previously shown evidence that polymorphisms within genes controlling leukotriene B4 (LTB4) production (ALOX5AP and LTA4H) are associated with asthma susceptibility in children. Evidence also suggests a potential role of LTB4 in COPD disease mechanisms including recruitment of neutrophils to the lung. The aim of the current study was to see if these SNPs and those spanning the receptor genes for LTB4 (LTB4R1 and LTB4R2) influence baseline lung function and COPD susceptibility/severity in smokers. Methods Eight ALOX5AP, six LTA4H and six LTB4R single nucleotide polymorphisms (SNPs) were genotyped in a UK Smoking Cohort (n = 992). Association with baseline lung function (FEV1 and FEV1/FVC ratio) was determined by linear regression. Logistic regression was used to compare smoking controls (n = 176) with spirometry-defined COPD cases (n = 599) and to more severe COPD cases (GOLD stage 3 and 4, n = 389). Results No association with ALOX5AP, LTA4H or LTB4R survived correction for multiple testing. However, we showed modest association with LTA4H rs1978331C (intron 11) with increased FEV1 (p = 0.029) and with increased FEV1/FVC ratio (p = 0.020). Conclusions These data suggest that polymorphisms spanning ALOX5AP, LTA4H and the LTB4R locus are not major determinants of baseline lung function in smokers, but provide tentative evidence for LTA4H rs1978331C (intron 11) in determining baseline FEV1 and FEV1/FVC ratio in Caucasian Smokers in addition to our previously identified role in asthma susceptibility.